Biodegradable materials with FDM technology under the aging effect of solar and saltwater exposure. - Valerga Puerta, Ana Pilar; Fernández-Sanz, Gema; Bañón-García, Fermín; Fernández-Vidal, Severo Raúl (Sage Journals, 2023)
The durability and degradation of polymers is very important for product design in terms of material choice. The degradation behavior of two biodegradable thermoplastic materials manufactured by 3D printing, Enviro ABS and PLA, was studied. The action of the sun and seawater was simulated to find out how they affect the properties of these materials over a period of 8 weeks. The yield strength, maximum elongation, ultimate tensile strength, and microscopy were analyzed, as well as dimensions and mass changes. These biodegradable materials were studied to conclude whether there is an environmentally friendly alternative to traditional ABS, being one of the most widely used petroleum-based plastics in industry and in fused deposition modeling (FDM) or fused filament fabrication (FFF). PLA showed a weight loss and increase in ultimate tensile stress on degradation by sunlight and a prolonged decrease in ultimate tensile stress on degradation by seawater due to humidity absorption. In contrast, Enviro ABS does not show a noticeable difference between the beginning and the end of the test, which leads to the conclusion that Enviro ABS is a good alternative to conventional ABS without forgetting the environmental effects that are currently involved in the manufacture, recycling and composting of this type of material
Keywords: Polímeros; Ciencia de los materiales; Materiales - Biodeterioro; Additive manufacturing; Polymer; Tensile Test; Environmental manufacturing